Mechanical-Chemical Characterization of the Effects of Type, Dosage, and Treatment Methods of Rejuvenators in Aged Bituminous Materials. Issue 3 (March 2020) - Nsengiyumva, Gabriel; Haghshenas, Hamzeh F.; Kim, Yong-Rak; Kommidi, Santosh Reddy
Proper use of rejuvenators can improve the properties and performance of aged asphalt mixtures; however, there is currently a lack of understanding on how rejuvenator treatment details, such as type-dosage of rejuvenators and blending-curing of rejuvenation, affect properties and performance characteristics. This study aims to investigate the effects of type, dosage, and treatment methods of rejuvenators when added into aged bituminous materials. To meet the goal, three rejuvenators, categorized by their production technology, were selected to improve a high-recycled asphalt pavement mixture by conducting various binder-level and mixture-level tests. For the binder-level testing, the performance grading (PG) method was used to primarily determine proper dosages targeting desired binder grades, and two chemical tests (Fourier-transform infrared spectroscopy and Saturate, Aromatic, Resin and Asphaltene) were conducted to examine chemical characteristics altered by rejuvenation and the further aging process. The selected dosage levels from the binder testing were then applied to mixture-level performance evaluation by conducting two tests: flow number for rutting and semicircular bending fracture for cracking. Test-analysis results indicated that although it can successfully determine the proper dosage range of rejuvenators, PG binder testing is limited to only assessing the effects of rejuvenators on mechanical properties; this can be better aided by integrating chemical characterization that provides a more in-depth material-specific rejuvenation process. Moreover, it appears that rejuvenation methods can alter the performance of aged mixtures. Therefore, the selection of rejuvenators and their implementation into practice should be carried out considering multiple aspects, not only its PG recovery.